La música en las misiones jesuitas en los llanos orientales colombianos 1725-1810 (1998)
Based in the original documents related to the expulsion of the Jesuit order in 1767, now housed at the Archivo General de la Nación (Bogotá, Colombia), this article aims at giving a first hand account of the musical activities developed in the Missions established by the Jesuits in the basin of the Casanare, Meta and Orinoco rivers in the Eastern lowland frontier between modern Colombia andVenezuela. Additional documents, also considered, allow us to complementour knowledge about the musical activities in these villages after the expulsionand estimate its impact in the traditional culture of that region.